Disclosure of extraordinary items and income smoothing behaviour in Malaysia - Shamsul Nahar Abdullah; Ku Nor Izah Ku Ismail; Nor Asma Lode (Penerbit Universiti Kebangsaan Malaysia, 2002)
This paper investigates disclosure practice of extraordinary items (EI) by listed companies in Malaysia during which the original standard on EI, SI 8 – Unusual and Prior Period Items and Changes in Accounting Policies was still in place. Until the adoption of the revised standard in 1997 (revised SI 8 and subsequently replaced by the MASB 3), the definition of EI given in the original SI 8 was very loose and it was opened to abuse. This paper also reports on whether EI disclosures were associated with income smoothing behaviour and the extent to which disclosure of EI was related to political costs, gearing and management interest. A total of 244 Kuala Lumpur Stock Exchange (KLSE) listed companies that disclosed EI at least once from 1991 to 1995 were included in this study. The study found that the incidence of EI was very high. However, the results showed no evidence of management using EI as a tool to smooth income. Further, EI disclosures were not explained by political costs, gearing and management interest. As there was no evidence of the use of EI to smooth income in Malaysia, the belief that the new standard (that restricts the definition of EI) would curb the practice of income smoothing is not relevant. The adoption of the new standard could only be expected to enhance the level of reporting comparability and consistency among Malaysian companies